Effect of furfuryl alcohol addition on the cure of furfuryl alcohol resin used in the glassy carbon manufacture - Gaefke, C. B.; Botelho, E. C.; Ferreira, N. G.; Rezende, M. C. (Wiley-Blackwell, 2007)
Glassy carbon can be manufactured practically without pores, named Monolithic Vitreous Carbon (MVC) or presenting up to 98% in transport pore volume, foam form, denominated Reticulated Vitreous Carbon (RVC). The glassy carbon processing is affected by some processing parameters, among them it can be cited the resin viscosity. The present work involves the optimization of RVC manufacture by monitoring the polyurethane (PU) foam impregnation with furfuryl alcohol resin with different viscosity values, which were obtained by dilution of the resin with different amounts of furfuryl alcohol. The resin samples used in the PU impregnation were characterized by thermal and rheological analyses. These results were correlated with scanning electron microscopy observations and compression test results of the impregnated polyurethane foam. The results show that the rheological behavior of the resin has significant influence on the polymerization step, affecting the homogeneity of impregnated foam and, consequently, its final properties, mainly the mechanical one. The impregnated foam prepared with the furfuryl alcohol resin diluted with 10% of furfuryl alcohol (eta = 11.4 Pa s) showed higher compression values (0.26 MPa). (c) 2007 Wiley Periodicals, Inc.
Keywords: reticulated vitreous carbon; furfuryl alcohol resin; thermal analyses; rheological analyses